Imaging in polymyalgia rheumatica - N. Possemato; C. Salvarani; N. Pipitone (PAGEPress Publications, 2018)
Polymyalgia rheumatica (PMR) is a chronic, inflammatory disorder of unknown cause clinically characterized by pain and prolonged morning stiffness affecting the shoulders and often the pelvic girdle and neck. Imaging has substantially contributed to defining PMR as a disease mainly involving extra-articular structures. This review article analyses the role of the different imaging techniques in the diagnosis and follow-up of patients with PMR with particular emphasis on the role of ultrasound, PET/CT and MRI.